SOCIAL HEALTH AND HEALTHY LIFESTYLE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article deals with the problem of individual and public health. The subjective and objective significance of such a social phenomenon as a healthy lifestyle is exposed in it. The problem of individual and public health is considered in the aspect of social responsibility. We define the concept of social responsibility as a category of social philosophy.